A clockwork orange [videorecording (DVD)] - Kubrick, Stanley; McDowell, Malcolm, 1943-; Magee, Patrick; Corri, Adrienne; Karlin, Miriam; Burgess, Anthony, 1917-1993 (Distributed by Warner Home Video, 2007)
"Stamping, whomping, stealing, singing, tap-dancing, violating, Derby-topped hooligan Alex has a good time -- at the tragic expense of others. His journey from amoral punk to brainwashed proper citizen and back again forms the dynamic arc of Stanley Kubrick's future-shock vision of the Anthony Burgess novel"--Container.